The last kids on earth and the zombie parade! - Brallier, Max; Holgate, Douglas (New York, New York : Viking, 2016)
The zombies are disappearing. This might seem like a good thing, since zombies eat your brains, but normal human kid Jack Sullivan is suspicious. He keeps hearing an eerie shrieking noise that seems to be almost summoning the zombies but to where, and for what (probably) foul purpose? Jack, his three best friends (maybe the only people left on Earth), and their pet monster Rover need to get to the bottom of this.
Keywords: Zombies -- Juvenile fiction; Monsters -- Juvenile fiction; Survival -- Juvenile fiction; Humorous fiction